OPTIMASI DESAIN SISTEM REFLEKTOR - MODERATOR LINEAR ACCELERATOR SEBAGAI SUMBER NEUTRON UNTUK BORON NEUTRON CAPTURE THERAPY (BNCT) MENGGUNAKAN SIMULASI MONTE CARLO N-PARTICLE 5 (MCNP5) - , DEYSI LISYE SENTINUWO; , Prof. Kusminarto, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
A research on Linear Accelerator (LINAC) reflector-moderator system design optimization as a neutron source on BNCT using MCNP5 has been conducted. Reflector-moderator system design optimization is used to obtain neutron beam output required by International Atomic Energy Agency (IAEA). The parameter variated in this research is the type as well as the thickness of material of reflector, moderator, filter, and gamma shield. Epithermal neutron flux as a result of reflector-moderator system optimization with 2 cm aperture has a value of 1,51 x 109 n/cm2s. Neutron beam output parameter obtained is 314 x 10-13 Gycm2/n for fast neutron component, 17,9 x 10-13 Gycm2/n for gamma contamination component, 0,05 for thermal neutron flux ratio and 0,71 for current component. These neutron beam output parameter are obtained at a reflector thickness of 20 cm Ni-nat, moderator thickness of 12 cm C-nat, and collimator thickness of 5 cm 6Li2CO3-polyethilene. In this system there are two parameters that do not meet the standards of the IAEA, a component of fast neutrons and gamma components. This reflector-moderator system can be applied to BNCT in vivo test. Keywords : BNCT, LINAC, Moderator-Reflector Sytem, MCNP5, Epithermal Neutron Flux